Astaxanthin-loaded proliposomes as a novel strategy to enhance stability, bioaccessibility, and antioxidant activity - Hang Xu; Zhiwen Lin; Ruojing Liu; Xinyu Guo; Huiling Hao; Shuaiya Liu; Wentao Su; Yukun Song; Mingqian Tan (Food Bioscience, 2026)

A Human-Ocean Health Index (HOHI) for integrated assessment under the cumulative effects of human activities and global change - Suzhen Yang; Qinhua Fang; Ruiqing Qin; Lin Liang; Wenyan Tang; Dian Zhang; Zhiyi Kan; Lusita Meilana; Huiling Liu (Marine Pollution Bulletin, 2026)

Arid–period floods and human adaptation promoted agricultural prosperity in the Neolithic heartland of the Middle Yellow River - Mengjing Li; Lin Chen; Yongxiu Lu; Rui Yang; Zili Wang; Huiling Sun; Aifeng Zhou (CATENA, 2026)

Enhanced adsorption of La(III) and Ce(III) onto phytic acid modified N-(2-hydroxyethyl) acrylamide - Zengjin Fu; Yan Hao; Tingrui Lin; Huiling Ma; Huazheng Sai; Hui Yang (Journal of Water Process Engineering, 2026)

Selenium regulates pyroptosis through the ROS-mtDNA-cGAS-STING axis to alleviate trimethyltin chloride-induced inflammation in chicken kidneys - Huiling Zheng; Xinyu Huo; Wenwen Zhang; Shuang Lou; Mingyue Li; Chenxi Huang; Kang Yang; Tong Xu; Hongjin Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

BMSC vesicles-encapsulated tannic acid-derived carbon dots efficiently target and orchestrate mitochondria mitophagy to promote cartilage repair in osteoarthritis - Rongjie Lin; Zhusong Huang; Weibin Chen; Quan Liu; Huiling Guo; Xingyu Lin; Yao Wang; Zhenbin Chen; Xi Zeng; Shishui Lin; Shaohuang Weng; Min Chen (Chemical Engineering Journal, 2026)

Synergistic sulfidation, biomineralization and neutralization enhancing efficient copper recovery and sustainable remediation of acid mine drainage - Huiling Tao; Liyuan Ma; Lanfang Lin; Jingkang Zhang; Peng Liu; Jianwei Zhou; Xingjie Wang (Journal of Environmental Chemical Engineering, 2026)

Nano-GlycOTAC eradicates Mycobacterium tuberculosis biofilms and rectifies iron metabolism to augment host antimicrobial immunity - Zhuojun He; Deliang Liu; Yang Zhou; Yao Zhao; Guiqin Dai; Zhiqiang Lin; Siwei Zhang; Xiafei Dai; Yuying Chen; Jinzhi Pan; Huiling Liu; Hong Yu; et al. (Chemical Engineering Journal, 2026)

Biomass-derived carbon quantum dots in wastewater treatment: Synthesis, sensing, and degradation - Luqiu Lin; Maryam Bayati; Chuxuan Zhang; Huiling Ong; Zhengkang Peng; Xun Gong; Minghou Xu (Journal of Environmental Management, 2026)

A novel approach to identify the spatial characteristics of ozone-precursor sensitivity based on interpretable machine learning - Huiling He; Kaihui Zhao; Zibing Yuan; Jin Shen; Yujun Lin; Shu Zhang; Menglei Wang; Anqi Wang; Puyu Lian (Journal of Environmental Sciences, 2026)

Dissolving microneedles loaded with Acanthopanax Senticosus-derived vesicles and PEI for antibacterial activity, cfDNA scavenging, anti-inflammation, and angiogenesis in diabetic wounds - Huiling Ye; Junze Tang; Wanting Liang; Yushan Li; Zhaoyi Ye; Jiasen Lin; Guining Cao; Yaoxun Zeng; Yu Sun; Meijing Wang; Ziqiao Li; Xin Cheng; et al. (Chemical Engineering Journal, 2025)

Strip clearcutting and replanting effects on soil organic carbon, microbial necromass carbon, and microbial carbon use efficiency in Chinese fir plantations - Xinran Zhao; Huiling Zhou; Hongwei Xu; Lin Xu; Chengming You; Li Zhang; Bo Tan; Zhenfeng Xu; Han Li; Lixia Wang; Sining Liu; Xinglei Cui; et al. (Plant and Soil, 2025)

A novel PADI6 splice-site variant induces non-canonical GC-AG splicing and embryonic arrest in humans - Huiling Hu; Jiaqi Sun; Fei Meng; Fei Gong; Ge Lin; Lizhi Leng; Wei Zheng (Functional & Integrative Genomics, 2025)

Single-electrode multiplex sensing via metal ion displacement method - Yiming Zhang; Zhi Chen; Songrui Wei; Huiling Lin; Yujun Zhang; Yingxia Liu; Jing Wang; Qi Gao; Defa Li; Han Zhang; Zhongjian Xie (Chemical Engineering Journal, 2025)

Fabrication of multicolor fluorescent perovskite-polymer composites and their application in information encryption - Yihui Lei; Huiling Liang; Lin Bai; Mingyu Jin; Juan Cheng; Tingcheng Li; Daohong Zhang; Sufang Chen; Zejun Xu (Chemical Engineering Journal, 2025)

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

CRISPR CLAMP: Attomolar level of multiple miRNAs - Yiming Zhang; Zhi Chen; Songrui Wei; Jing Wang; Yujun Zhang; Huiling Lin; Hai Fu; Yingxia Liu; Qi Gao; Han Zhang; Zhongjian Xie (Chemical Engineering Journal, 2025)

Sustainable lipids production in algal-bacterial consortia under low light intensity: Regulation of light–dark on fatty acid composition - Huiling Jiang; Houyu Lin; Naif Abdullah Al-Dhabi; Hongyuan Liu; Taiping Qing; Bo Feng; Wangwang Tang; Peng Zhang (Chemical Engineering Journal, 2025)

Data-driven optimization of nose profiles for water entry impact load reduction - Kai Lv; Enfan Lin; Yongze Liu; Zongbao Chen; Yexian Wang; Ming He; Jiale Yan; Pengyu Lv; Yantao Yang; Hongyuan Li; Huiling Duan (Ocean Engineering, 2025)

Human settlement and destructive activities disrupt the positive contribution of dust to plant biomass growth over the past 2000 years - Lin Chen; Youliang Huang; Menghan Qiu; Zhilun Li; Rui Yang; Mengjing Li; Huiling Sun; Lixiong Xiang; Shanjia Zhang; Xiaozhong Huang; Aifeng Zhou (Global and Planetary Change, 2025)

Evaluating the involvement and mutual interaction of wbp2 and yap in embryogenesis with an emphasis on liver function in zebrafish embryos - Nikita Lykov; Huiling Wang; Mogellah John Panga; Zhanxiang Du; Ziyi Chen; Shitian Chen; Lin Zhu; Ye Zhao (Tissue and Cell, 2024)

Cognition of grape cluster picking point based on visual knowledge distillation in complex vineyard environment - Jinhai Wang; Xuemin Lin; Lufeng Luo; Mingyou Chen; Huiling Wei; Lijia Xu; Shaoming Luo (Computers and Electronics in Agriculture, 2024)

Microplastics emerge as a hotspot for dibutyl phthalate sources in rivers and oceans: Leaching behavior and potential risks - Lujian Lin; Bo Yuan; Huiling Liu; Yue Ke; Weifeng Zhang; Hanyi Li; Haoliang Lu; Jingchun Liu; Hualong Hong; Chongling Yan (Journal of Hazardous Materials, 2024)

Amelioration of radiation cystitis by tetrahedral framework nucleic acid nanostructures functionalized with quercetin - Wei Wang; Ran Yan; Lede Lin; Liao Peng; Yang Xiong; Huiling Chen; Xiaoshuai Gao; Kun Liu; Liang Zhou; Yunfeng Lin (Chemical Engineering Journal, 2024)

Structural characteristics of maceral components in exinite-rich coal and their interaction during the direct liquefaction - Jiachen Yu; Lin Lin; Yuanzhe Wang; Zhenyu Liu; Qingya Liu; Xiangen Shan; Huiling Guo; Hezheng Gui; Lei Shi (Fuel, 2024)

Fe, Mn-Prussian blue analogue@MXene composites for efficient photocatalytic peroxydisulfate-activated degradation of tetracycline hydrochloride and photoelectrochemical desalination - Huiling Hu; Huan Lin; Xuncai Chen; Yupeng Pan; Xuewei Li; Zile Zhuang; Hedong Chen; Xing Wang; Min Luo; Kezhi Zheng; Liguo Zhang; Fuming Chen (Chemical Engineering Journal, 2023)

Highly-oxidizing Au@MnO2−X nanozymes mediated homogeneous electrochemical detection of organophosphorus independent of dissolved oxygen - Huiling Zeng; Hailan Chen; Bing Yang; Junyi Zeng; Lin Meng; Donglin Shi; Liang Chen; Youju Huang (Journal of Hazardous Materials, 2023)

Persulfate promoted visible photocatalytic elimination of bisphenol A by g-C3N4–CeO2 S-scheme heterojunction: The dominant role of photo-induced holes - Yin Xu; Xin Tang; Yan Xiao; Huiling Tang; Heng Lin; Yujuan Lv; Hui Zhang (Chemosphere, 2023)

A metal-organic framework (MOF) and graphene oxide (GO) based peroxymonosulfate (PMS) activator applied in pollutant removal - Meiyun Qi; Ping Lin; Qiyu Shi; Huiling Bai; Huan Zhang; Weihuang Zhu (Process Safety and Environmental Protection, 2023)

Convective-scale ensemble forecasts of the heavy precipitation of Typhoon Lekima (2019) in Zhejiang Province - Fanyu Xu; Huiling Yuan; Limin Lin; Wenbin Chen (Atmospheric Research, 2023)

Effects of aerosols on the forecasting of Mei-yu frontal storms over the Yangtze–Huai River valley - Lin Liu; Huiling Yuan; Yi Deng; Jing Ren; Yongqing Bai; Chunguang Cui (Atmospheric Research, 2023)

NIR-responsive hollow germanium nanospheres mediate photothermal/photodynamic therapy and restrain immunosuppression to cooperatively eradicate primary and metastatic tumors - Qilin Li; Huiling Fan; Yunruo Xu; Miaodeng Liu; Jia Liu; Luming Xu; Meizhen Zou; Qian Cheng; Yan Zhang; Tao Liang; Lin Shi; Xianluo Hu; et al. (Chemical Engineering Journal, 2023)

Injectable Host-Guest supramolecular hydrogel Co-Delivers hydrophobic and hydrophilic agents for enhanced wound healing - Jie Xu; Kangning Wang; Yanyan Li; Yue Li; Bingxin Li; Hangqi Luo; Huiling Shi; Xueran Guan; Ting Zhang; Yixiao Sun; Feng Chen; Huacheng He; et al. (Chemical Engineering Journal, 2023)

Genomic Analysis and Molecular Characteristics in Carbapenem-Resistant Klebsiella pneumoniae Strains - Suying Zhao; Xingyi Qiu; Yiting Tan; Min Xu; Xiaotong Xu; Yulai Ge; Huiling Cao; Min Li; Yuxin Lin; Zhan Zhang; Lei Li; Qian Wu (Current Microbiology, 2022)

Clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in children in China - Wen Song; Qingwen Shan; Yue Qiu; Xianyao Lin; Chunhui Zhu; Zhiqiang Zhuo; Caihong Wang; Jianning Tong; Rui Li; Chaomin Wan; Yu Zhu; Minxia Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Invasive Salmonella infections result in a significant burden of disease including morbidity, mortality, and financial cost in many countries. Besides typhoid fever, the clinical impact of non-typhoid Salmonella infections is increasingly recognized with the improvement of laboratory detection capacity and techniques. A retrospective multicenter study was conducted to analyze the clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in hospitalized children in China during 2016–2018. A total of 130 children with invasive Salmonella infections were included with the median age of 12 months (range: 1–144 months). Seventy-nine percent of cases occurred between May and October. Pneumonia was the most common comorbidity in 33 (25.4%) patients. Meningitis and septic arthritis caused by nontyphoidal Salmonella (NTS) infections occurred in 12 (9.2%) patients and 5 (3.8%) patients. Patients < 12 months (OR: 16.04) and with septic shock (OR: 23.4), vomit (OR: 13.33), convulsion (OR: 15.86), C-reactive protein (CRP) ≥ 40 g/L (OR: 5.56), and a higher level of procalcitonin (PCT) (OR: 1.05) on admission were statistically associated to an increased risk of developing meningitis. Compared to 114 patients with NTS infections , 16 patients with typhoid fever presented with higher levels of CRP and PCT ( P < 0.05). The rates of resistance to ampicillin, sulfamethoxazole/trimethoprim, ciprofloxacin, and ceftriaxone among Salmonella Typhi and NTS isolates were 50% vs 57.3%, 9.1% vs 24.8%, 0% vs 11.2%, and 0% vs 9.9%, respectively. NTS has been the major cause of invasive Salmonella infections in Chinese children and can result in severe diseases. Antimicrobial resistance among NTS was more common.

Microbiological profiles and antimicrobial resistance patterns of pediatric bloodstream pathogens in China, 2016–2018 - Yue Qiu; Junwen Yang; Yiping Chen; Jinhong Yang; Qingxiong Zhu; Chunhui Zhu; Shuangjie Li; Jing Liu; Chaomin Wan; Yu Zhu; Minxia Chen; Yi Xu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Characteristics and health risk assessments of heavy metals in PM2.5 in Taiyuan and Yuci college town, China - Xiaofeng Liu; Zhilei Wang; Huiling Bai; Shuting Zhang; Ling Mu; Lin Peng (Air Quality, Atmosphere & Health, 2020)

Gene structure, recombinant expression and function characterization of Siniperca chuatsi Fsrp‐3 - Jianhua Wang; Jia Cheng; Yulong Li; Huiling Yan; Ping Wu; Xin Zhu; Li Liu; Lin Chen; Wuying Chu; Jianshe Zhang (Journal of Fish Biology, 2019)
A full‐length complementary (c)DNA sequence encoding follistatin‐related protein 3 ( fsrp‐3 ) was determined from skeletal muscle in Chinese mandarin fish Siniperca chuatsi , its molecular structure was characterised and its function suggested. The putative structure of S. chuatsi Fsrp‐3 contains an N‐terminal domain and two follistatin domains. Quantitative reverse‐transcription (qRT)‐PCR assays revealed that fsrp‐3 messenger (m)RNA was differentially expressed among assayed tissues and was highly expressed in heart and intestine. fsrp‐3 mRNA exhibited increasing expression from the larval to the juvenile stage (500 g). To investigate the potential function of S. chuatsi fsrp‐3 in muscle growth, we constructed a Fsrp‐3 prokaryotic expression system and injected the purified Fsrp‐3 fusion protein into the dorsal muscle. Fsrp‐3 administration significantly influenced cross‐section area, satellite cell activation frequency and nuclear density of S. chuatsi muscle fibres. Following Fsrp‐3 treatment, the expression of myogenic regulatory factors was up‐regulated and decline in the expression of myostatin was observed. The study revealed that Fsrp‐3 may affect muscle growth by regulating myogenic regulatory factor expression and antagonizing myostatin function to initiate satellite cell activation and differentiation in S. chuatsi .

Upregulated TRIM32 correlates with enhanced cell proliferation and poor prognosis in hepatocellular carcinoma - Xiaopeng Cui; Zhipeng Lin; Yuyan Chen; Xiaofei Mao; Wenkai Ni; Jinxia Liu; Huiling Zhou; Xiaohang Shan; Lingling Chen; Jiale Lv; Zhongyi Shen; Chengwei Duan; et al. (Molecular and Cellular Biochemistry, 2016)

Health risk assessment of toxic VOCs species for the coal fire well drillers - Yulong Yan; Lin Peng; Na Cheng; Huiling Bai; Ling Mu (Environmental Science and Pollution Research, 2015)

Characteristics of hopanoid hydrocarbons in ambient PM10 and motor vehicle emissions and coal ash in Taiyuan, China - Feng Han; Junji Cao; Lin Peng; Huiling Bai; Dongmei Hu; Ling Mu; Xiaofeng Liu (Environmental Geochemistry and Health, 2015)

Genome-Wide Identification of microRNAs and Their Targets in Cold-Stored Potato Tubers by Deep Sequencing and Degradome Analysis - Yongbin Ou; Xun Liu; Conghua Xie; Huiling Zhang; Yuan Lin; Meng Li; Botao Song; Jun Liu (Plant Molecular Biology Reporter, 2015)

Occurrence and particle-size distributions of polycyclic aromatic hydrocarbons in the ambient air of coking plant - Xiaofeng Liu; Lin Peng; Huiling Bai; Ling Mu; Chongfang Song (Environmental Geochemistry and Health, 2014)

Th17 cell expansion in gastric cancer may contribute to cancer development and metastasis - Zhaoliang Su; Yingkun Sun; Haitao Zhu; Yueqin Liu; Xin Lin; Huiling Shen; Jianguo Chen; Wenlin Xu; Huaxi Xu (Immunologic Research, 2014)

Profiling of StvacINV1 Expression in Relation to Acid Invertase Activity and Sugar Accumulation in Potato Cold-Stored Tubers - Yongbin Ou; Botao Song; Xun Liu; Yuan Lin; Huiling Zhang; Meng Li; Hui Fang; Jun Liu (Potato Research, 2013)

A new isoform of thioredoxin h group in potato, SbTRXh1, regulates cold-induced sweetening of potato tubers by adjusting sucrose content - Tianjiu He; Botao Song; Jun Liu; Xia Chen; Yongbin Ou; Yuan Lin; Huiling Zhang; Conghua Xie (Plant Cell Reports, 2012)

Modulation of gene expression in cold-induced sweetening resistant potato species Solanum berthaultii exposed to low temperature - Xia Chen; Botao Song; Jun Liu; Jianwen Yang; Tianjiu He; Yuan Lin; Huiling Zhang; Conghua Xie (Molecular Genetics and Genomics, 2012)

Eukaryotic translation elongation factor 1 delta inhibits the ubiquitin ligase activity of SIAH-1 - Huiling Wu; Yan Shi; Ying Lin; Wei Qian; Yao Yu; Keke Huo (Molecular and Cellular Biochemistry, 2011)

Identification and mapping of a thermo-sensitive genic self-incompatibility gene in maize - Xinge Lin; Huiling Xie; Zhangying Xi; Yanmin Hu; Guangyuan Zhao; Liujing Duan; Zongyou Hao; Zonghua Liu; Jihua Tang (Genes & Genomics, 2009)